Short-Term Alteration of Soil Physicochemical Characteristics Induced by Biochar Application on a Ferric Acrisol - Jochebed Kaki Torgbenu; Godfred Boateng; Felix Osei Kwarteng; Stephen Ardey Mensah; Edward Benjamin Sabi; Peace Korshiwor Amoatey; Peter Amoako Ofori; Stella Owusu-Nketia; Anthony Raphael Simpson; Selorm Yaotse Dorvlo; Emmanuel Essien; Evans Asenso (Scientifica)
Biochar (incinerated organic waste by-product) has shown promise in enhancing soil fertility and agricultural productivity. Soil quality plays an essential role in the success of agricultural activities, with soil enhancement being crucial for optimizing crop yields and fostering soil fertility. An experiment with different biochar types was arranged in a randomized complete block design. The biochar [coconut husk (CH) biochar and sugarcane bagasse (SB) biochar] was evenly hand mixed with the soil after plowing to 30 cm depth. A one-time application of biochar was done. There was a total of six treatments: SB biochar, SB biochar plus nitrogen (N), phosphorus (P), potassium (K) (SB + NPK), CH biochar, CH biochar plus NPK (CB + NPK), NPK, and control (CT), with three replicates for each treatment. The area of each plot was 3 m2 (3 m × 1 m) to assess the effects of biochar application on the soil physical and chemical characteristics of Ferric Acrisol with cabbage (Fortune F1 variety) as a test crop in Ghana. Soil bulk density, porosity, pH, organic carbon (OC), available N, total P, available K, available calcium (Ca), electrical conductivity (EC), and cation exchange capacity (CEC) were determined. CH and SB addition improved soil bulk density (1.21 g·cm−3 and 1.29 g·cm−3), leading to a significant (p<0.05) improvement in the total porosity (54.29% and 51.10%), respectively, at 0–30 cm soil depth compared to the presoil condition (1.5 g·cm−3). Additionally, CH and SB significantly (p<0.05) impacted the soil chemical characteristics and fertility of the tested soil. The results showed that biochar application is crucial for C sequestration, reduction in pH (SB-7.36 and CH-7.44 compared to the presoil condition (4.93) at 0–30 cm soil depth), and soil fertility enhancement. Applying biochar to soils can therefore be considered a potential solution to improve soil fertility for sustainable crop production.